Signalling mechanisms that regulate metabolic profile and autophagy of acute myeloid leukaemia cells - Pereira, Olga (2018)
Acute myeloid leukaemia (AML) comprises a heterogeneous group of hematologic neoplasms characterized by diverse combinations of genetic, phenotypic and clinical features representing a major challenge for the development of targeted therapies. Metabolic reprogramming, mainly driven by deregulation of the nutrient-sensing pathways as AMPK, mTOR and PI3K/AKT, has been associated with cancer cells, including AML cells, survival and proliferation. Nevertheless, the role of these metabolic adaptations on the AML pathogenesis is still controversial. In this work, the metabolic status and the respective metabolic networks operating in different AML cells (NB-4, HL-60 and KG-1) and their impact on autophagy and survival was characterized. Data show that whereas KG-1 cells exhibited preferential mitochondrial oxidative phosphorylation metabolism with constitutive co-activation of AMPK and mTORC1 associated with increased autophagy, NB-4 and HL-60 cells displayed a dependent glycolytic profile mainly associated with AKT/mTORC1 activation and low autophagy flux. Inhibition of AKT is disclosed as a promising therapeutical target in some scenarios while inhibition of AMPK and mTORC1 has no major impact on KG-1 cells' survival. The results highlight an exclusive metabolic profile for each tested AML cells and its impact on determination of the anti-leukaemia efficacy and on personalized combinatory therapy with conventional and targeted agents.